The Low Cost Airline Consumer Price Sensitivity. An Investigation on The Mediating Role of Promotion and Trust in Brand - Sihite, Janfry; Harun, Tabby Wihasari; Nugroho, Arissetyanto (International Research Journal of Business Studies, 2014)
The ASEAN Open Sky Policy is one of ASEAN policy to open the airspace between the ASEAN member countries. Aviation services based companies including the Low Cost airlines will experience tight competition among ASEAN airline companies. This research aim to explore the effect of price on customer loyalty through the mediating role of promotion and trust in brand. The original sample collected from 100 Indonesian low-cost airline Citilink consumer that just arrived in Soekarno-Hatta International Airport, the bootstrapped techniques conducted for 500 sub-samples and further analyzed with structural equation modelling partial least square. The research findings support the low cost airline consumer price sensitivity, furthermore price affect the trust in brand more severe compared with the promotion. Price effect fully mediated through the trust in brand and promotion toward the consumer loyalty. Further research should consider the sensitivity of price to elaborate the decision making process for the low cost airline consumer.